Undertaking Rehabilitation Research During the COVID-19 Pandemic: Emergent Strategies From a Trainee-Faculty Workshop - Noguchi, Kenneth S.; Nguyen, Linda; Mehdipour, Ava; Wiley, Elise; Saunders, Stephanie; Moncion, Kevin; Reid, Julie C.; Bakaa, Nora; Garcia Diaz, Laura; Van Damme, Jill; D'Amore, Cassandra; Kumurenzi, Anne; et al. (Frontiers in Rehabilitation Sciences, 2022)
Background The COVID-19 pandemic has disrupted everyday rehabilitation research. Many academic institutions have halted in-person human research including rehabilitation sciences. Researchers are faced with several barriers to continuing their research programs. The purpose of this perspective article is to report the results of an interdisciplinary workshop aimed at understanding the challenges and corresponding strategies for conducting rehabilitation research during the COVID-19 pandemic. Methods Twenty-five rehabilitation researchers (17 trainees and eight faculty) attended a 2-h facilitated online workshop in to discuss challenges and strategies they had experienced and employed to conduct rehabilitation research during the COVID-19 pandemic. Results Rehabilitation researchers reported challenges with (1) pandemic protocol adjustments, (2) participant accessibility, and (3) knowledge dissemination, along with corresponding strategies to these challenges. Researchers experienced disruptions in study outcomes and intervention protocols to adhere to public health guidelines and have suggested implementing novel virtual approaches and study toolkits to facilitate offsite assessment. Participant accessibility could be improved by engaging community stakeholders in protocol revisions to ensure equity, safety, and feasibility. Researchers also experienced barriers to virtual conferences and publication, suggested opportunities for smaller networking events, and revisiting timeframes for knowledge dissemination. Conclusion This perspective article served as a catalyst for discussion among rehabilitation researchers to identify novel and creative approaches that address the complexities of conducting rehabilitation research during the COVID-19 pandemic and beyond.